Basic Buddhist concepts - Mizuno, Kōgen, 1901-2006 (Kosei Pub. Co., 1987)
One of the world's oldest and greatest religions, Buddhism -- like its companions, Christianity and Islam -- has experienced schism and division which scatter its teachings among separate sects, nations and sets of ritual practice. Nonetheless, it is possible to identify common teachings which form the essence of Buddhist belief. This book provides lucid explanations of such fundamental concepts as the Three Treasures, the seals of the law, the Four Noble Truths, the Eightfold Path, the law of causation, and the threefold learning -- teachings that all Buddhists honor, which bare the heart of this complicated and magnificently profound religion.